The Oxford handbook of sovereign wealth funds - Cumming, Douglas; Wood, Geoffrey E., 1945-; Filatotchev, Igor; Reinecke, Juliane (Oxford : Oxford University Press, 2017)
Sovereign Wealth Funds have become increasingly powerful and influential investors. Their increasing role, and unusual character as both political and market actors, raise a number of issues with regard to finance, politics, regulation, and international business. This handbook draws together the growing but fragmented research on SWFs.
A Financial Force to be Reckoned With? An Overview of Sovereign Wealth Funds / Veljko Fotak, Xuechen Gao, William L. Megginson -- Strangers Are Not All Danger: SWF Investment in the Energy Industry / Di Wang -- Investment Terms and Level of Control of China's Sovereign Wealth Fund in its Portfolio Firms / Jing Li -- Sovereign Wealth Funds and Private Equity / Douglas Michael Wright, Kevin Amess -- Sovereign Wealth Funds and the Resource Curse - Resource funds and governance in resource-rich countries / Jędrzej George Frynas -- The Norwegian Government Pension Fund-Global and the Implications of its Activities for Stakeholders / Geoffrey Wood, Noel O'Sullivan, Marc Goergen, Marijana Baric -- The Australian Future Fund / Xi-Chong Xu -- Is it possible to avoid the St. Augustine Syndrome of fiscal procrastination? The Case of Chile / Eric Parrado -- The China Investment Corporation: From Inception to Sideline / Christopher Balding, Kevin Chastagner -- Sovereign Wealth Funds and the Global Political Economy of Trust and Legitimacy / Gordon L. Clark, Adam D. Dixon -- Sovereign Wealth Funds in the Persian Gulf States / Gawdat Bahgat -- Sovereign Funds and Domestic Political Risk / Paul Rose -- From Financialization to Vulture Developmentalism: South-North Strategic Sovereign Wealth Fund Investment and the Politics of the 'Quadruple Bottom Line' / Daniel Haberly -- Introducing Sovereign Wealth Funds / Douglas Cumming, Igor Filatotchev, Juliane Reinecke, Geoffrey Wood -- Sovereign Wealth Funds and Foreign Policy / Kathryn C. Lavelle -- Sovereign Wealth and the Extraterritorial Manipulation of Corporate Conduct: A Multifaceted Paradigm in Transnational Law / Salar Ghahramani -- Sovereign Wealth Fund Investment and Firm Volatility / April Knill, Nathan Mauck -- Sovereign Wealth Funds: Investment Choices and Implications around the World / Nuno Fernandes -- Sovereign Development Funds: The Governance and Management of Strategic Investment Institutions / Peter Bruce-Clark, Ashby H.B Monk -- Co-investments of sovereign wealth funds in private equity / Joseph A. McCahery, F. Alexander de Roode -- The Use of Debt by Sovereign Wealth Fund / Stefano Lugo, Fabio Bertoni -- Sovereign wealth fund investments and industry performance: Evidence from Europe / t
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 2, 2017).
Keywords: Sovereign wealth funds